Preclinical Evaluation of Bispecific Adaptor Molecule Controlled Folate Receptor CAR-T Cell Therapy With Special Focus on Pediatric Malignancies - Lu, Yingjuan J.; Chu, Haiyan; Wheeler, Leroy W.; Nelson, Melissa; Westrick, Elaine; Matthaei, James F.; Cardle, Ian I.; Johnson, Adam; Gustafson, Joshua; Parker, Nikki; Vetzel, Marilynn; Xu, Le-Cun; et al. (Frontiers in Oncology, 2019)
Chimeric antigen receptor (CAR)-T cell therapy has transformed pediatric oncology by producing high remission rates and durable responses in CD19+ B-cell malignancies. This scenario is ideal as CD19 expression is homogeneous and human blood provides a favorable environment for CAR-T cells to thrive and destroy cancer cells (along with normal B cells). Yet, CAR-T cell therapies for solid tumors remain challenged by fewer tumor targets and poor CAR-T cell performances in a hostile tumor microenvironment. For acute myeloid leukemia and childhood solid tumors such as osteosarcoma, the primary treatment is still “heavy-duty” chemotherapy that falls short of expectation especially for relapsed and refractory conditions. To join this endeavor, we aim to develop a CAR-T adaptor molecule (CAM)-based therapy that uses a bispecific small-molecule ligand EC17, fluorescein isothiocyanate (FITC) conjugated with folic acid, to redirect FITC-specific CAR-T cells against folate receptor (FR)-positive tumors. As previously confirmed in rodents as well as in human clinical studies, EC17 penetrates solid tumors within minutes and is retained due to high affinity for the FR, whereas unbound EC17 rapidly clears from the blood and from receptor-negative tissues. When combined with a rationally designed CAR construct, EC17 CAM was shown to trigger CAR-modified T cell activation and cytolytic activity with a low FR threshold against tumor targets. However, maximal cytolytic potential correlated with i) functional FR levels (in a semi-log fashion), ii) the amount of effector cells present, and iii) tumors’ natural sensitivity to T cell mediated killing. In tumor-bearing mice, administration of EC17 CAM was the key to drive CAR-T cell activation, proliferation and persistence against FR+ pediatric hematologic and solid tumors. In our modeling systems, cytokine release syndrome (CRS) was induced under specific conditions, but the risk of severe CRS could be easily mitigated or prevented by applying intermittent dosing and/or dose-titration strategies for the EC17 CAM. Our approach offers the flexibility of antigen control, prevents T cell exhaustion, and provides additional safety mechanisms including rapid reversal of severe CRS with intravenous sodium fluorescein. In this paper, we summarize the translational aspects of our technology in support of clinical development.